Компактный аппаратно-программный комплекс для диагностики электронных регуляторов САУ ГТД в эксплуатации - Буряченко, Анна Григорьевна; Бурунов, Дмитрий Сергеевич; Немченко, Ольга Владимировна (Avìacìjno-kosmìčna tehnìka ì tehnologìâ, 2021)
The relevance of creating a compact hardware and software complex is analyzed to ensure a full check of the operability of electronic regulators of gas turbine engines, in particular, the AI-35 engine, developed by SE "Ivchenko-Progress". The article describes the composition and functionality of the device developed by Element JSC, which was named “Complex of software and hardware for imitation of actuators and engine sensors”. The complex under consideration is intended both for autonomous use and for work as part of an automated workstation (AWS), which in turn is a part of the AI-35 engine semi-natural simulation stand. A feature of the complex is that it contains built-in mathematical models of the engine, electric drive pump-fuel regulator, as well as sensors installed on the engine. Based on the results of processing digital signals from an automated workstation or a touchscreen display, the complex generates output analog and frequency signals – rotor speed, pressure at the compressor outlet, the temperature at the compressor inlet, temperature of gases at the outlet of the turbine. The complex also generates control signals for the imitation of igniting pyro plugs and a fuel pyrovalve, in particular, it provides an imitation of their "combustion" by breaking the circuit. The built-in touchscreen display makes it easy for the operator conducting the governor and engine tests to use the complex as intended. With the help of the display, without using a PC, the operator can manually control the process of simulating the issuance of a command to start the engine by changing the values of the rotor speed, form various modes of engine operation, setting the appropriate parameters, simulate engine surge, etc. The functionality of the developed complex provides debugging of GTE control algorithms and subsequent tests of the regulator.